Tax Service Quality And Sanctions On Individual Taxpayer Compliance: The Moderating Role Of Tax Awareness - Ilfa Damayanti; Della Fadhilatunisa; Puspita Hardianti Anwar (Journal of Applied Taxation and Policy, 2025)
This study aims to test the effect of the quality of tax authorities' services on individual taxpayer compliance, test tax sanctions on individual taxpayer compliance, test whether taxpayer awareness is able to moderate the relationship between the quality of tax authorities' services and individual taxpayer compliance, and test whether taxpayer awareness is able to moderate tax sanctions with individual taxpayer compliance. This study is a type of quantitative research with a quantitative descriptive approach. The location of this study is the North Makassar Pratama Tax Service Office. The sample in this study was 100 using a simple random sampling technique with the Slovin formula which has the criteria, namely individual taxpayers who work as permanent employees in the government or private sector, individual taxpayers who carry out freelance work in the form of business activities in the scope of MSMEs and individual taxpayers who have consulted or have experienced the services provided by tax officials (tax authorities). The data used is the type of primary data obtained through the distribution of questionnaires. The results of the study indicate that the quality of tax authorities' services and tax sanctions have a significant positive effect on individual taxpayer compliance. Analysis of the moderation variables using the absolute difference value approach shows that taxpayer awareness cannot moderate the influence of the quality of tax services on individual taxpayer compliance and can moderate the influence of tax sanctions on individual taxpayer compliance.